Qualification juridique du harcèlement moral en France - Gaëlle Encrenaz; Loïc Lerouge (Perspectives Interdisciplinaires sur le Travail et la Santé)
Analyzing litigation in moral harassment cases raises research questions that legal methods cannot always provide an answer for. By contrast, epidemiological methods can provide detailed descriptions and analyses of the elements associated with the court order. Using the JURICA French database, we analyzed judgements for moral harassment at work that were handed down by the Court of Appeal in Aquitaine, France, and identified the elements associated with the court order. Of the 136 selected judgements, 38 dealt with a moral harassment situation as determined by the judges. A situation of moral harassment was more frequently concluded when the victim was a woman, when a consultation with a medical doctor was followed by sick leave, when discrimination was indicated, and when management decisions were questioned.